(untitled) (International Journal of Architecture and Urbanism, 2023)
In areal scope, certain concentration of industry brings positive effects that raise the effectiveness of regional economic development, but it also results in various negative aftereffects such as ecological environmental destruction in the area when it is over certain limit. Furthermore, it loses dominance of the economic geographical location of the area and causes serious loss from the state viewpoint by resulting the problem of industrial relocation in the economic geographical space. In this paper, we solved methodological problem of evaluating industrial concentration district in the area in order to protect negative effects due to high concentration of industry that causes acute issues with environment and resources recently. In order to solve this problem, we established evaluation index system for evaluation of the industrial concentration district in the area, studied the methodology to search industrial concentreation district with the use of the analytic function of influence scope and aggregate district etc. in GIS and then searched indusrial concentraion district in 00 industrial area by applying this method. We should no longer arrange new industry in such industrial concentration district in the future and have to rationally control the industrial structure by realizing the industrial relocation